The effect of education based on health belief model on dietary behavior of Coronary Artery Bypass Graft patients - Farzaneh Zighaimat; Abas Ebadi; Ali.Akbar Karimi-Zarchi; Nastaran Moradi; Zahra Hajiamini; Soudabeh Mehdizadeh (Iran University of Medical Sciences, 2010)
Background and Aim: Coronary artery disease (CAD) is the most prevalent cardiovascular disease (CAD) and the leading cause of mortality in industrialized and developing countries. It is also the first cause of mortality in Iran. People with CAD need changes in lifestyle, because the disease is chronic.. In this study health belief model (HBM) as one of the theories related to changing lifestyle is used to change behaviors related to dietary performance in Coronary Artery Bypass Graft (CABG) patients. The aim of this study was to examine the effects of education based on health belief model on dietary behavior of Coronary Artery Bypass Graft patients   Material and Method : In this quasi- experimental study, 64 CABG patients were recruited through purposive sampling and randomly assigned to either control or experimental group. Data gathering tools included questionnaire and checklist. At first, questionnaire and checklist were completed by subject in both groups. Then, the educational protocol was implemented for experimental group. They also took education notes. Two months after the intervention, questionnaire and checklist were completed again by subject in both groups.   Results : There was a significant improvement in knowledge level, perceived severity, benefits, barriers, and total performance about dietary in experimental group (P<0.05). A statistically significant correlation was found between dietary performance of both group and age, educational degree, and family history variables, meaning that patients with greater age and level of education and positive family history had better dietary performance. (P 0.05).   Conclusion : Education based on HBM leads to improving knowledge level, perceived severity and benefits and deceived barriers and eventually, dietary performance.